Thermomechanical and Shape Memory Properties of SCF/SBS/LLDPE Composites - Wang, Yong-kun; Tian, Wen-chao; Zhu, Guang-ming; Xie, Jian-qiang (Chinese journal of polymer science, 2016)
A thermally triggered shape memory polymer composite was prepared by blending short carbon fiber（SCF） into a blend of poly（styrene-b-butadiene-b-styrene） triblock copolymer（SBS）/linear low density polyethylene（LLDPE） prior to curing. These composites have excellent processability compared with other thermosets. The dynamic mechanical analysis（DMA） and differential scanning calorimetry（DSC） were investigated to assess the thermomechanical properties of the SCF/SBS/LLDPE composite. Scanning electron microscope（SEM） imaging of the samples was performed to show the distribution of the SCF in the composite. The study specifically focused on the effect of SCF on the shape memory behavior of the SCF/SBS/LLDPE composite. The results indicated that the large amount of SCF significantly improved the mechanical property of the polymer composites while not damaging the shape memory performance. The SCF/SBS/LLDPE composites exhibited excellent shape memory behavior when the SCF content was less than 15.0 wt%. Moreover, the shape fixity ratio and shape recovery time of the SCF/SBS/LLDPE composites increased with the SCF content.